(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Truong DD. 2021. Estimating residents’ willingness to pay for wetland conservation using contingent valuation: the case of Van Long Ramsar Protected Area, Vietnam. Biodiversitas 22: 4784-4793. Willingness to pay (WTP) for wetland conservation is an important basis for designing market-based wetland protection strategies and sustainable wetland management. The main objective of this study is to estimate villagers’ WTP for wetland conservation in Van Long Wetland Protected Area, Vietnam, and analyze factors influencing WTP. A questionnaire survey based on the dichotomous contingent valuation method (CVM) was conducted at seven communes surrounding Van Long Ramsar Protected Area (VLPA). The results showed that the local people in the studied area appreciate the roles of the wetland in preserving landscape values, supporting livelihoods, and transmitting values ??to future generations. The value of biodiversity conservation and the value of water filtration and regulation are perceived to a lesser extent in terms of the importance of conservation. Of the 384 respondents, 96% are WTP for wetland conservation at different levels. With the parametric model, the average value of WTP ranges from 300,000 to VND 328,000 VND /family/year. In the non-parametric model, the average of WTP is from 338,000 to 359,000 VND/family/year. The probability of environmental response’ that willing to pay for conservation is closely related to their awareness, family income and payment amount. The results also showed optimistic points that the local people are willing to contribute to improving wetland quality. In a general sense, the results of this study make good contributions to the literature related to WTP for wetland conservation in developing countries.